Prospective study of brentuximab vedotin in relapsed/refractory Hodgkin lymphoma patients who are not suitable for stem cell transplant or multi-agent chemotherapy - Walewski, Jan; Hellmann, Andrzej; Siritanaratkul, Noppadol; Ozsan, Guner Hayri; Ozcan, Muhit; Chuncharunee, Suporn; Goh, Ai Sim; Jurczak, Wojciech; Koren, Jan; Paszkiewicz-Kozik, Ewa; Wang, Bingxia; Singh, Shalini; et al. (British journal of haematology, 2018)
Some patients with relapsed/refractory Hodgkin lymphoma (HL) are not considered suitable for stem cell transplant (SCT) and have a poor prognosis. This phase IV study (NCT01990534) evaluated brentuximab vedotin (1·8 mg/kg intravenously once every 3 weeks) in 60 patients (aged ≥18 years) with CD30-positive relapsed/refractory HL, a history of ≥1 prior systemic chemotherapy regimen, who were considered unsuitable for SCT/multi-agent chemotherapy. Primary endpoint was overall response rate (ORR) per independent review facility (IRF). Secondary endpoints included duration of response (DOR), progression-free survival (PFS) per IRF, overall survival (OS), proportion proceeding to SCT and safety. The ORR was 50%, with 12% CR; 47% proceeded to SCT. Median DOR was 4·6 months and median duration of CR was 6·1 months. After a median follow-up of 6·9 and 16·6 months, median PFS and OS were 4·8 months (95% confidence interval, 3·0-5·3) and not reached, respectively; estimated OS rate was 86% at 12 months. Most common adverse events (≥10%) were peripheral neuropathy (35%), pyrexia (18%), diarrhoea and neutropenia (each 10%). Brentuximab vedotin showed notable activity with a safety profile consistent with known toxicities, and may act as a bridge to SCT, enabling high-risk patients who achieve suboptimal response to frontline/salvage chemotherapy/radiotherapy to receive potentially curative SCT.
Keywords: následné studie; lidé; mladiství; Adult; Brentuximab Vedotin; Middle Aged; phase IV; Risk Factors; transplantace kmenových buněk; prospektivní studie; míra přežití; Hodgkinova nemoc; Immunoconjugates; Female; relapsed/refractory; Survival Rate; novel anti-tumour agents; Adolescent; Humans; protokoly protinádorové kombinované chemoterapie; Follow-Up Studies; Prospective Studies; lidé středního věku; přežití bez známek nemoci; mužské pohlaví; Hodgkin lymphoma; Hodgkin Disease; brentuximab vedotin; Disease-Free Survival; ženské pohlaví; Male; Aged; Stem Cell Transplantation; dospělí; imunokonjugáty; Antineoplastic Combined Chemotherapy Protocols; rizikové faktory; senioři